Active gyroscopic stabilizer to mitigate vibration in a multimegawatt wind turbine - Soleymani, Mehdi; Norouzi, Mahdi (Wiley, 2020)
One of the main concerns in developing large wind turbines, especially offshore, is their cost‐effectiveness versus traditional power sources. Significant dynamic loads are applied to the tower and the foundation of a multimegawatt wind turbine. Any reduction in the loads can reduce the size of the structure and, consequently, the turbine's cost. In this paper, a novel structural control application is proposed to mitigate the transmitted vibrations to a multimegawatt turbine tower to decrease the tower base shear forces and overturning moments. For this purpose, a hybrid passive/active gyro stabilizer is designed and incorporated into the NREL baseline 5‐MW wind turbine. Furthermore, two controllers, including a proportional integral differential (PID), as the baseline controller, and a nonlinear fuzzy logic controller (FLC) as the main and nonlinear controllers, have been designed and implemented to the turbine model. The structural control systems are implemented into the turbine model by cosimulating ADAMS and Simulink. The results reveal that the application of the proposed stabilizer can significantly reduce the overturning moment at the base of the tower compared to the reference NREL 5‐MW model
Keywords: wind turbine; structure; gysroscopic stabilizier; fuzzy control